PERIOPERATIVE MEDICAL NUTRITIONAL THERAPY IN A SEVERELY MALNOURISHED PATIENT WITH AMPULLA OF VATER CARCINOMA POST WHIPPLE PROCEDURE: A CASE REPORT - Ratha, I Putu Prayoga (Perhimpunan Dokter Gizi Klinik Indonesia, 2026)
Abstract Background : The ampulla of Vater carcinoma is a rare gastrointestinal malignancy but has a better prognosis than pancreatic cancer. Severe malnutrition is common in patients with gastrointestinal cancer and worsens clinical outcomes. Objective: To report the implementation of structured perioperative nutrition therapy in a severely malnourished patient with carcinoma of the ampulla of Vater. Methods: Case report of a 51-year-old woman with severe malnutrition and obstructive jaundice, who underwent a Whipple procedure . Nutritional status assessment was performed using Subjective Global Assessment (SGA), anthropometry, and hand grip strength (HGS). Perioperative nutritional therapy was carried out in stages, with clinical and laboratory monitoring. Results: Nutrition therapy was started preoperatively with the ERAS method and continued gradually postoperatively through enteral and parenteral routes, until the patient was able to accept a full oral diet and vitamin supplementation. The target energy of 1840 kcal and protein 78 g/day was achieved within 7 days. Clinical status and physical function improved during treatment. Conclusion: Appropriate perioperative nutritional therapy supports metabolic recovery, improves nutritional status, and enhances clinical outcomes in patients with advanced gastrointestinal cancer undergoing major surgery. Keywords : severe malnutrition, ampullary carcinoma , perioperative nutritional medical therapy, Whipple procedure